(untitled) (Research, Society and Development, 2020)
The present work aims to evaluate "in silico" hydroxychloroquine and its analogs obtained and make a comparative study between them, taking into account the pharmacokinetic, pharmacodynamic and toxicological parameters. In the pharmacokinetic and toxicological analysis, the online server PreADMET was used to make predictions based on the structure of the molecule and in the pharmacodynamic analysis, another online server was used, the Swiss TargetPrediction where the targets that the molecules were linked to and the probability of binding were observed. According to the predictions that were made, we can see that the two analogs were slightly better than hydroxychloroquine. Regarding pharmacokinetics, the analogue JW 01 showed an absorption rate (Caco2) better than the prototype and no inhibition of cytochrome P450 enzymes. In pharmacodynamics, the two analogs presented a better profile than the prototype, with JW 01 presenting lower link probabilities with some receptors and JW 02 did not bind to any of them. In toxicology the molecules showed mutagenicity and no carcinogenicity, in the risk of inhibition of the hERG gene they presented medium risk, and the analogue JW 02 was less toxic than the other molecules in the tests with marine animals.